PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA FLASH CARD TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK SEKOLAH DASAR - Adela Fauziah; Nurdiansyah Nurdiansyah; Nadia Tiara Antik Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking skill, though crucial for communication, is often neglected in elementary language education, which tends to prioritize reading and writing. Recognizing that students' speaking abilities require enhancement, this study aimed to analyze the impact of the Contextual Teaching and Learning (CTL) model, supported by flash cards, and the Jigsaw Cooperative Learning model, also with flash cards, on the speaking skills of third-grade elementary students. A comparative analysis of the improvements between these two models was also a key objective.Utilizing a Quasy Experiment with a non-equivalent control group design, the research involved two classes, each comprising 25 students. The experimental class received instruction using the CTL model with flash cards, while the control class utilized the Jigsaw model, similarly aided by flash cards. Data collection involved pre-tests, post-tests, and observation sheets. Statistical analysis, encompassing descriptive and inferential methods, was performed using IBM SPSS version 30.0 and Microsoft Excel 2021.The findings revealed significant insights: 1) The CTL model with flash cards demonstrated a 70.6% effect on improving speaking skills; 2) The Jigsaw model with flash cards showed a 45.7% effect. Furthermore, the average N-Gain for the experimental class (CTL) was 0.65 (moderate), while the control class (Jigsaw) registered 0.54 (moderate). A t-test confirmed a significant difference in speaking skill improvement between the two groups. Consequently, the CTL model assisted by flash cards proved more effective than the Jigsaw model with flash cards. This study recommends adopting the flash card-assisted CTL model as an effective alternative for enhancing elementary school students' speaking skills.